Plasmonic nanomaterials with responsive polymer hydrogels for sensing and actuation. (26th April 2022) - Diehl, Fiona; Hageneder, Simone; Fossati, Stefan; Auer, Simone K.; Dostalek, Jakub; Jonas, Ulrich
Abstract : The combination of plasmonic nanomaterials with responsive polymer hydrogels yields novel materials and devices with exceptional synergetic properties, which are reviewed in the context of applications, such as sensing and actuation. Abstract : Plasmonic nanomaterials have become an integral part of numerous technologies, where they provide important functionalities spanning from extraction and harvesting of light in thin film optical devices to probing of molecular species and their interactions on biochip surfaces. More recently, we witness increasing research efforts devoted to a new class of plasmonic nanomaterials that allow for on-demand tuning of their properties by combining metallic nanostructures and responsive hydrogels. This review addresses this recently emerged vibrant field, which holds potential to expand the spectrum of possible applications and deliver functions that cannot be achieved by separate research in each of the respective fields. It aims at providing an overview of key principles, design rules, and current implementations of both responsive hydrogels and metallic nanostructures. We discuss important aspects that capitalize on the combination of responsive polymer networks with plasmonic nanostructures to perform rapid mechanical actuation and actively controlled nanoscale confinement of light associated with resonant amplification of its intensity. The latest advances towards the implementation of such responsive plasmonic nanomaterials are presented, particularly covering the field of plasmonic biosensing that utilizes refractometric measurements as well as plasmon-enhanced optical spectroscopy readout, optically driven miniature soft actuators, and light-fueled micromachines operating in an environment resembling biological systems.